Academics knowledge about tooth bleaching: technical and ethical issues - Mariana Dias FLOR-RIBEIRO; Natalia Simora RODRIGUES; Fabricio Luscino Alves de CASTRO; Daphne Camara BARCELLOS; Flávia Bittencourt PAZINATTO (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: The aim of this study was to evaluate the level of knowledge of UFES dental students about home bleaching treatment. Methods: As a methodology, a descriptive and cross-sectional study was carried out through the application of practice to 109 students, containing questions about home tooth whitening, technical care and possible complications of the treatment. Data were tabulated and submitted to descriptive statistics. Results: Of the total number of students, 88.99% said they knew the factors that limit or contraindicate the bleaching treatment, 16.51% of students recognize hydrogen peroxide as a possible inducer of oral cancer, 30.27% of the students had their teeth whitened inside the University, 44.03% had their teeth whitened outside the University without professional supervision. In addition, 56.88% believe anamnesis and clinical examination are necessary before the bleaching treatment. Conclusion: It is concluded that students have limited knowledge about certain points of at-home tooth whitening. Students know the risk factors of bleaching treatment, except regarding hydrogen peroxide being a possible inducer of oral cancer. It can be inferred that academics highlight the importance of associating the clinical examination with the patient's anamnesis before performing the bleaching treatment. Most students have had their teeth whitened outside the University, which calls attention to reinforce knowledge about the ethical issues of the profession.